2020
DOI: 10.1186/s12886-020-01419-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficacy of reduced-fluence and standard-fluence photodynamic therapy in the treatment of polypoidal choroidal vasculopathy

Abstract: Background: The EVEREST II study reported superior polyp closure rates and visual outcomes using combination standard photodynamic therapy (PDT) with intravitreal ranibizumab in the treatment of polypoidal choroidal vasculopathy (PCV). The optimal PDT protocol remains controversial and it is postulated that less intensive PDT strategies may reduce complications. We aimed to compare the efficacy of reduced and standard-fluence PDT. Methods: Case-control review of 38 consecutive PDT-naïve macular PCV patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…PDT can reduce the thickness of the macula in the early stage of treatment, although it has been reported to result in sight threatening complications such as subretinal, vitreous and suprachoroidal hemorrhage, as well as tears and rips of the RPE. While a recently study showed none of the patients in either the standard-fluence PDT group nor the reduced-fluence PDT group suffered from any major complication, and the effect in each group was comparable ( 12 ). On the other hand, the intravitreal injection of anti-VEGF agents can significantly improve vision in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…PDT can reduce the thickness of the macula in the early stage of treatment, although it has been reported to result in sight threatening complications such as subretinal, vitreous and suprachoroidal hemorrhage, as well as tears and rips of the RPE. While a recently study showed none of the patients in either the standard-fluence PDT group nor the reduced-fluence PDT group suffered from any major complication, and the effect in each group was comparable ( 12 ). On the other hand, the intravitreal injection of anti-VEGF agents can significantly improve vision in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…20 29 30 A recent case-control review comparing reduced and standard fluence PDT in 38 patients with macular PCV showed a comparable visual gain and anatomical outcome with a polyp closure rate of 77.8% in the RF-PDT group. 30 Although the effects of RF-PDT have been studied in context of PCV, the evidence comes from small sampled cases series and this study will give us the opportunity to evaluate the effect of RF-PDT more formally in a clinical trial setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, hemorrhagic complications after PDT or anti-VEGF injection are not uncommon. The incidence of hemorrhagic complications such as subretinal hemorrhage or breakthrough VH are reported to range from 0% to 33% after PDT monotherapy and 0.6% to 23% after combination therapy of PDT and anti-VEGF injections [6,[13][14][15][16][17][18][19][20][21][22][23]. Hirami et al suggested that laser irradiation during PDT may occlude choroidal vessels,…”
Section: Plos Onementioning
confidence: 99%